Knowledge domain and hotspots concerning photosensitive hydrogels for tissue engineering applications: A bibliometric and visualized analysis (1996-2022) - Fu, Hongxun; Wang, Hao; Jiang, Lin; Zhang, Yupeng; Tong, Haibin; Meng, Guixian; Sun, Meiyan (Frontiers in Bioengineering and Biotechnology, 2022)
The aim of tissue engineering (TE) is to replace the damaged tissues or failed organs, or restore their missing functions. The important means to achieve this aim is to integrate biomaterials and life elements. Hydrogels are very attractive biomaterials in the field of TE. In particular, engineering extracellular matrices (ECMs) formed by photosensitive hydrogels have captivated much attention, because photopolymerization has many advantages over traditional polymerization approaches, such as rapidity of reaction, spatiotemporal controllability of polymerization process, and operability at physiological temperature, especially it can realize the fabrications of engineering ECMs in the presence of living cells. There have been many excellent reviews on the applications of photosensitive hydrogels in TE in recent years, however, it is inevitable that researchers may have left out many important facts due to exploring the literature from one or a few aspects. It is also a great challenge for researchers to explore the internal relationships among countries, institutions, authors, and references from a large number of literatures in related fields. Therefore, bibliometrics may be a powerful tool to solve the above problems.As an advanced method of paper analysis, bibliometrics focuses on bibliometric analysis in terms of countries, institutions, journals, authors, keywords and cited documents . A bibliometric and visualized analysis of publications concerning the photosensitive hydrogels for TE applications was performed, and the knowledge domain, research hotspots and frontiers in this topic were identified according to the analysis results.